Time Is Ripe for Targeting Per- and Polyfluoroalkyl Substances-Induced Hormesis: Global Aquatic Hotspots and Implications for Ecological Risk Assessment - Sun, Tao; Ji, Chenglong; Li, Fei; Wu, Huifeng (Environmental science & technology, 2024)
Globally implemented ecological risk assessment (ERA) guidelines marginalize hormesis, a biphasic dose–response relationship characterized by low-dose stimulation and high-dose inhibition. The present study illuminated the promise of hormesis as a scientific dose–response model for ERA of per- and polyfluoroalkyl substances (PFAS) represented by perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS). A total of 266 hormetic dose–response relationships were recompiled from 1237 observations, covering 30 species from nine representative taxonomic groups. The standardized hormetic amplitudes followed the log-normal probability distribution, being subject to the limits of biological plasticity but independent of stress inducers. The SHapley Additive exPlanations algorithm revealed that the target endpoint was the most important variable explaining the hormetic amplitudes. Subsequently, quantitative frameworks were established to incorporate hormesis into the predicted no-effect concentration levels, with a lower induction dose and a zero-equivalent point but a broader hormetic zone for PFOS. Realistically, 10,117 observed concentrations of PFOA and PFOS were gathered worldwide, 4% of which fell within hormetic zones, highlighting the environmental relevance of hormesis. Additionally, the hormesis induction potential was identified in other legacy and emerging PFAS as well as their alternatives and mixtures. Collectively, it is time to incorporate the hormesis concept into PFAS studies to facilitate more realistic risk characterizations.